Analisis Risiko Kesehatan Akibat Konsumsi Tomat (Lycopersicon esculentum) yang Mengandung Residu Profenofos di Kabupaten Gowa - Abdul Majid HR. Lagu; Habibi Habibi; Syahrul Basri (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2015)
Tomato is of high nutritional value so highly favored by the entire community. In tomato production activities can not be separated from the use of pesticides. This study aims to determine the health risk from consumption of tomato (Lycopersicon esculentum) containing residues of profenofos in Subdistrict Tamaona at Gowa Regency. This study is an observational method to study the draft Environmental Health Risk Analysis. Profenofos concentrations were measured using Gas Chromatography (GC), whereas body weight, intake rate, and frequency of exposure quantitatively measured through questionnaires to interview 100 respondents to calculate Intake profenofos and health Risk Quotient (RQ). Profenofos concentration in the vegetable tomatoes detected in samples I, II, and V, while the samples III and IV are not detected, the highest concentration in the sample V is 0.5234 mg/kg and the average concentration of 0.37003 mg/kg. Based on these results, the concentration of profenofos in tomato vegetable still below the MRL established SNI 2009 is 2.0 mg/kg. For the analysis of the results showed a total of 88 respondents Carcinogens RQ has an average value of RQ ≤ 1 and 12 respondents had RQ values > 1. For Non-Carcinogenic RQ many as 18 respondents had an average RQ values ≤ 1 and 82 respondents had RQ values> 1. Group with RQ values ≤ 1 categorized as a safe group, whereas the group with RQ > 1 is called risk groups to the effects of carcinogens or non-carcinogens disease. Management of health risk reduction needs to be done as they see the risk of exposure to carcinogens and disease profenofos both non-carcinogenic diseases. Keywords: Environmental Health Risk Analysis, Profenofos, Tomato, Tamaona